Federated ecology: from federated data to federated intelligence - Fei-Yue WANG; Yanfen WANG; Yizhu CHEN; Yonglin TIAN; Hongwei QI; Xiao WANG; Weishan ZHANG; Jun ZHANG; Yong YUAN (智能科学与技术学报)
In view of the widespread isolated data island in the era of big data, the basic framework of federated ecology was proposed, and its construction and operation mechanism were discussed.Federated ecology was based on the premise of controllable data privacy, supported by blockchain technology and driven by federated intelligence.It realized data federation by means of federated control, and realized federated service through federated management.Federated ecology provides a new way to address the problem of isolated data island, gives full play to the potential of big data and artificial intelligence, and then realizes federated intelligence.